Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1177/0091415017730812
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Environment, Residential Satisfaction, and Depressive Symptoms Among Older Adults in Residential Care Homes

Abstract: Burgeoning evidence has shown that neighborhood environments are related to depressive symptoms in the older population. Older adults living in residential care homes may be more vulnerable to environmental characteristics. The current study sought to understand how institutionalized older adults relate to environmental factors and residential satisfaction in terms of depressive symptoms. Data were collected from a cross-sectional national survey of 1,429 Chinese elders living in residential care homes. The fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…For example, epidemiological studies indicated that the prevalence of depression symptoms among the elderly in nursing homes was 90.2% in Iran, 16 81.8% in Taiwan, 17 29.6% in London 18 and 46.1% in the Mainland China. 19 The association between sleep quality and depression symptoms among the elderly is complex, bidirectional and not entirely understood. However, many studies have suggested that elderly people with some sleep disturbance are more likely to develop depression symptoms than younger people with some sleep disturbance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, epidemiological studies indicated that the prevalence of depression symptoms among the elderly in nursing homes was 90.2% in Iran, 16 81.8% in Taiwan, 17 29.6% in London 18 and 46.1% in the Mainland China. 19 The association between sleep quality and depression symptoms among the elderly is complex, bidirectional and not entirely understood. However, many studies have suggested that elderly people with some sleep disturbance are more likely to develop depression symptoms than younger people with some sleep disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…For example, epidemiological studies indicated that the prevalence of depression symptoms among the elderly in nursing homes was 90.2% in Iran, 16 81.8% in Taiwan, 17 29.6% in London 18 and 46.1% in the Mainland China. 19 …”
Section: Introductionmentioning
confidence: 99%
“…Living in the community with higher satisfaction of its environment is more conducive to promoting the individual's mental health [29,56], which further shows that the subjective positive perception of community living environment can protect people from the negative psychological impact of social and economic inequality. Based on these findings, it is necessary for future research to pay more attention to the promotion of community environment on potential positive psychological effects.…”
Section: Discussionmentioning
confidence: 99%
“…20 major parameters were constructed based on their way of living, satisfaction level at the current location to bring out their level of interactions with the surrounding community members. These parameters have been modified from the works of Hur and Morrow-Jones (2008), Shaw et al (2017), Liu, Ouyang, Chong, and Wang (2018) and others who have worked with the psychological impacts of urban dwellers and a detailed statistical analysis is still in progress by the authors. Respondents were primarily separated into neighbourhood communities which included families who owned their houses and lived through generations in the same area and those who have been tenants in the same locality for generations while the respondents of the gated communities included residents of the newly built middle income group (MIG) apartments and high income group building complexes (HIG).…”
Section: Residential Conversion and Public Liaisonmentioning
confidence: 99%